Wearable Sensors for Health Monitoring: Technologies, Applications, Challenges, and Future Perspectives - Abrori, Syauqi Abdurrahman (Bina Nusantara University, 2025)
This article presents the state of the art and future outlook for wearable sensors for health monitoring, with emphasis on their roles in tracking physiological, biochemical, motion, and environmental parameters. Wearable sensors have moved beyond activity monitoring to facilitate clinical applications like chronic disease management, remote monitoring, and mental health evaluation. Four sensors are presented, with the sensing principle, formats, and actual-world application. System architectural elements like data acquisition, wireless communication, on-device and cloud processing, and user interface are addressed. The latest advancements like multi-modal sensor fusion, self-sustaining platforms, integration of machine learning, and skin-conformable electronics are also outlined. Wearable technology holds promise and is plagued with accuracy, battery life, privacy of data, and compatibility with health information systems. These hindrances need to be overcome if broader clinical integration and global accessibility are to take place. Avenues for development include energy-autonomous sensors, personalized feedback systems, and digital twin integration, which have promising potential for making early intervention, preventive care, and decentralized healthcare delivery possible. This overview provides a general background to researchers, developers, and clinicians striving for the next generation of digital health solutions.